(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article aims to explore the complex landscape of placental vascular pathology in the setting of maternal COVID-19 infection, and to highlight the challenges and opportunities for clinicians, researchers, and health professionals in protecting pregnant women and their well-being.